Wear Resistance Study of Nitrided ASS 316L Above The Sensitization Temperature of 1200oC - Abd Rashid, Muhamad Naim (IRC, 2016)
Nitriding is known as one of the way for surface treatment in order to increase the wear resistance of the materials. There are a lot of publication that studied on the effect of nitriding towards the wear resistance performance of the material. However, the effectiveness of nitriding of the nitrided Austenitic Stainless Steel 316L above the sensitization temperature were not studied enough. This present work is aimed to study the effective nitriding time on wear resistance improvement of 316L Austenitic Stainless Steel. The heat treatment times were 4H ,8H and 12H under nitriding temperature of 1200ºC .The sample of the test is fabricated by ASTM C1624 Standard Test Method for Adhesion Strength and Mechanical Failure Modes of Ceramic Coating by Quantitative Single Point Scratch Testing.